Photochemical Synthesis of Solution‐Processable Graphene Derivatives with Tunable Bandgaps for Organic Solar Cells. Issue 5 (2nd December 2014) - Stylianakis, Minas M.; Sygletou, Maria; Savva, Kyriaki; Kakavelakis, George; Kymakis, Emmanuel; Stratakis, Emmanuel
<x xml:space="preserve">Abstract</x> A photochemical route for the facile synthesis of tunable bandgap graphene‐based derivatives from graphene oxide (GO) through controlled laser irradiation in liquid phase is presented. The method is facile and fast, yielding these materials within 2 h and with excellent long‐term stability. It makes use of photogenerated‐solvated electrons that give rise to GO reduction, accompanied by preferential attachment of the desired functional unit, intentionally dispersed into the precursor GO solution. As a proof of concept, laser GO‐ethylene‐dinitro‐benzoyl (LGO‐EDNB) was photochemically synthesized and utilized as the electron acceptor material in organic bulk heterojunction solar cells (OSCs) with the poly[N‐9′‐heptadecanyl‐2, 7‐carbazole‐alt‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)] as the electron donor. The graphene derivatives are highly dispersible in organic solvents used in OSCs, while their energy levels can be readily tuned upon fine‐tuning of the bandgap, which is directly related to the irradiation dose applied during the synthesis process. The utilization of LGO‐EDNB with a band gap of 1.7 eV, and a resultant lowest unoccupied molecular orbital level of 4.1 eV, leads to maximum open‐circuit voltage of 1.17 V and to power conversion efficiency (PCE) of 2.41%, which is the highest PCE for graphene‐based electron acceptors to date.